Short term effects of the REAL media e-learning media literacy substance prevention curriculum: An RCT of adolescents disseminated through a community organization. (1st September 2020) - Greene, Kathryn; Ray, Anne E.; Choi, Hye Jeong; Glenn, Shannon D.; Lyons, Rachel E.; Hecht, Michael L.
Highlights: Youth using REAL media increased self-efficacy to counterargue at three-month posttest. Youth using REAL media increased injunctive norms at three-month posttest. Engaging youth with e-learning analysis of ATOD advertising can be effective. Partnering with community groups such as 4-H is a viable alternative for prevention. E-learning approaches to substance prevention can be easily disseminated. Abstract: Background: The primary aim of this study was to evaluate the short-term effects of testing an e-learning program to reduce adolescent substance use and abuse. Early initiation of substance use is linked to a variety of negative outcomes, thus effective intervention programs are needed. One approach is to use media literacy to capitalize on adolescents' immersion with media in a variety of forms. We developed, implemented, and tested an engaging substance use prevention program by collaborating with a youth-oriented community partner (4-H). Methods: 639 middle adolescents from nine U.S. states participated in an RCT of REAL media. Participants completed a series of online surveys and were randomized to use an online substance prevention program (REAL media) or serve as control (delayed program use). Self-report surveys were administered at three points in time. This short-term evaluation uses data from the pretest (Time 1) and short-term posttest three-month surveys, which measured demographics, self-efficacy to counterargue, and injunctive and descriptive substance use norms. Results: Participants who completed the REAL media program reported increased self-efficacy to counterargue and decreased positive injunctive norms compared to control participants who did not complete the program. No significant differences were observed for descriptive norms. Conclusions: We found support for the REAL media program in changing key predictors of youth substance use demonstrating (1) the efficacy of media literacy interventions targeting adolescents and (2) that e-learning substance use prevention efforts can be adapted for and implemented through community organizations.